RNA Sequencing Reveals Small and Variable Contributions of Infectious Agents to Transcriptomes of Postmortem Nervous Tissues From Amyotrophic Lateral Sclerosis, Alzheimer’s Disease and Parkinson’s Disease Subjects, and Increased Expression of Genes From Disease-Activated Microglia - Bennett, James P.; Keeney, Paula M.; Brohawn, David G. (Frontiers in neuroscience, 2019)
Nervous tissues from both humans with neurodegenerative diseases (NDD) and animals with genetic models of human NDD, such as rare monogenic causes of Amyotrophic Lateral Sclerosis (ALS), Alzheimer's disease (AD), and Parkinson's disease (PD), show activated microglia, suggesting a potential causal role for inflammation in pathogenesis of NDD. We performed paired-end (PE) RNA sequencing (RNA seq) of total RNA's extracted from frozen sections of cervical spinal cords from ALS and CTL subjects, frontal cortical gray matter ribbons of AD and CTL subjects, and ventral midbrains of PD and CTL subjects. Trimmed PE reads were aligned against the hg38 human transcriptome using Tophat2/Bowtie2 (ALS) or HISAT2 (AD and PD) and quantitated with Cufflinks. PE reads were also aligned using Bowtie2 against genomes from representative species of and sp. T6 (parasitic infectious agents), and (tick-vector borne agents), and and , agents causing chronic gingivitis. Primary aligned reads of each agent in each tissue sample were quantitated with SAMtools. We found small percentages (<0.1%) of transcriptomes aligned with , , , and genomes and larger percentages aligned with (0.1-0.2%) and sp. T6 (1.0-1.1%) genomes. In AD specimens, but in no others, primary aligned transcriptome percentages, although small, approached significance for being greater in AD compared to CTL samples for ( = 0.067) and ( = 0.068). Genes' expressions in postmortem tissues of AD and ALS but not PD revealed significant changes among disease-associated microglial (DAM) genes. Infectious agents' transcripts can be detected in RNA seq reads of both NDD and CTL tissues and vary from agent to agent. Expressions of Stage 1 and Stage 2 DAM genes significantly changed, suggesting the presence of Stages 1 and 2 DAM in our NDD tissue samples.